2015
DOI: 10.1007/s11307-015-0873-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Somatostatin Receptor 2-Targeting PET Tracers in the Detection of Mouse Atherosclerotic Plaques

Abstract: Our results demonstrate superior applicability for [(68)Ga]DOTANOC and [(68)Ga]DOTATATE in the detection of atherosclerotic plaques compared to [(18)F]FDR-NOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 37 publications
3
64
1
Order By: Relevance
“…Two studies demonstrated autoradiographic 68 Ga-DOTATATE binding within macrophage-rich aortic atherosclerotic plaques in mice 6, 7. Five retrospective analyses of PET scans from patients who underwent imaging for oncological indications reported significant statistical relationships between vascular SST 2 signals and clinical CVD factors, including older age, male sex, hypercholesterolemia, presence of calcified coronary plaque, prior CVD events, and Framingham risk score calculated using BMI 8, 9, 10, 18, 19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies demonstrated autoradiographic 68 Ga-DOTATATE binding within macrophage-rich aortic atherosclerotic plaques in mice 6, 7. Five retrospective analyses of PET scans from patients who underwent imaging for oncological indications reported significant statistical relationships between vascular SST 2 signals and clinical CVD factors, including older age, male sex, hypercholesterolemia, presence of calcified coronary plaque, prior CVD events, and Framingham risk score calculated using BMI 8, 9, 10, 18, 19.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical 6, 7 and retrospective 8, 9, 10 studies suggest that gallium-68-labeled [1,4,7,10-tetraazacyclododecane- N , N ', N '', N '''-tetraacetic acid]- d -Phe 1 , Tyr 3 -octreotate (DOTATATE), a PET ligand with high-specificity binding affinity for SST 2 (11), may be superior to [ 18 F]FDG in marking macrophage activity, particularly in the coronary arteries. However, robust evaluation of 68 Ga-DOTATATE in atherosclerosis is lacking.…”
mentioning
confidence: 99%
“…68 Ga-DOTATATE, a specific sst2 receptor agonist, therefore was thought to have the potential to be a surrogate marker of inflammation to study plaque biology. This has been recently validated in 2 preclinical murine experiments (apolipoprotein 2/2 mice model) at a tissue level (24,25). Four recent studies examined the potential role of these in atherosclerosis, retrospectively in patients with neuroendocrine tumors.…”
Section: Rationale For Study Of 68 Ga-dotatate In Atherosclerosismentioning
confidence: 97%
“…It is also known that vessels can express somatostatin receptors under certain conditions (22,23). Recently, 2 preclinical murine studies have demonstrated the potential of somatostatin receptor PET in atherosclerosis imaging (24,25). Retrospective human studies with these tracers have also shown promise (26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Rinne et al [39] compared several PET probes targeting SSTR-2 in a mouse model and indicated the superior applicabilities of 68 Ga-DOTANOC and 68 Ga-DOTATATE in the detection of atherosclerotic plaques compared with 68 Ga-FDR-NOC. Several clinical studies have also indicated the potential roles of 68 Ga-DOTATATE and 64 Cu-DOTATATE in oncology patients and patients undergoing endarterectomy [6][7][8].…”
Section: Pet/spect Probes For Imaging Inflammatory Cellsmentioning
confidence: 99%